Penerimaan Diri Mahasiswa Introvert Di Media Sosial Instagram - Darwis , Nurul Fajrianti; Latief, Rahmawati; Muhammad , Firdaus (AL-IRSYAD AL-NAFS: JURNAL BIMBINGAN DAN PENYULUHAN ISLAM, 2024)
This study aims to determine the forms of self-acceptance of introverted students on Instagram social media and to find out the obstacles faced by introverted students in building a self-acceptance process through Instagram social media. The type of research used is descriptive qualitative research using the phenomenological method. Data collection techniques are carried out through in-depth interviews, observation and documentation. Informants are students of the Communication Science Department Faculty of Dakwah and Communication UIN Alauddin class of 2020 who were selected based on the purpose sampling technique, so that researchers obtained five people, namely Nursyahbani Tri Sulistiyawati Amar, Tifani Amalia, A. Muh. Fadlial Mushahif, Candra Nugraha, and Sumarni. Data analysis was carried out with three stages, namely data reduction, data presentation, and conclusion drawing. The results of this study indicate that there are seven forms of self-acceptance of introverted students on Instagram, namely the use of Instagram to express feelings and experiences, confidence in visual expression of Instagram filters, implicit expression of emotions, expression of creativity as a reflection of self, expression of togetherness through Instagram content, self-expression through comedy content, and expressive of followers and following content on Instagram. Then it was found that there were five obstacles faced by introverted students on Instagram social media, namely social comparisons, hesitation in expressing themselves, oversharing, negative comments, and consideration in expressing themselves on Instagram.